Analisis Perhitungan Harga Pokok Produksi Roti dengan Menggunakan Metode Full Costing pada UMKM San Roti - Wahyu Bagus Putra; Yulinartati; Elok Fitriya (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
In Indonesia, many companies or MSMEs do not use proper financial records, especially in calculating the cost of production. Even though this calculation is really needed so that there are no errors in calculating the cost of production. The method used in this research is the Full Costing method because this method is required to include all costs incurred in the production process, including variable overhead costs and fixed overhead. It is from this background that this research was conducted with the title ""Analysis of the Calculation of the Cost of Production of Bread Using the Full Costing Method in SAN Roti MSMEs" Lumajang. This research uses a descriptive qualitative approach where the aim is to explain systematically the research focus which includes calculating the cost of production using the full costing method. The object of this research is a bakery. Data was collected by means of observation, interviews and documentation. The research results show that calculations using the full costing method produce lower costs than calculations according to San Roti. This is because in the calculations made by UMKM San Roti there are costs that are not included in the calculation, namely asset depreciation costs. Meanwhile, in calculations using the full costing method, asset depreciation costs are calculated and included in the calculation, resulting in different production costs.